Islamic Insurance: How Far has it been Researched? - Widigdo, Aslam Mei Nur (Fara'id and Wealth Management, 2023)
The revival of the Islamic finance business is marked by the number of Islamic financial institutions operating such as in the fields of banking, insurance, leasing, pawnshops, hotels, cooperatives and other types of financial institutions. The public is more familiar with Islamic banking in the practice of Islamic finance. But actually, Islamic economics is not synonymous with Islamic banking. Another Islamic financial institution that follows the trend of growth and development is Islamic insurance. This study aims to determine the development map and trend of Islamic Insurance studies published by reputable journals in the field of Islamic Economics and finance. The data analyzed were more than 353 publications of Scopus indexed research publications. The results showed that the keywords that often appear in research on the theme of Islamic Insurance are divided into 7 specific study clusters. The results also fully explain tree-map, trend topic, thematic map and thematic evolution. In the future, topics related to Islamic insurance need to be of concern to researchers because it is one of the least researched topics by Islamic finance academics compared to other topics.